Home respiratory polygraphy in obstructive sleep apnea syndrome in children: Comparison with a screening questionnaire. (April 2021) - Maggio, Albane B.R.; Beghetti, Maurice; Cao Van, Hélène; Grasset Salomon, Carole; Barazzone-Argiroffo, Constance; Corbelli, Regula
Abstract: Objectives: The prevalence of obstructive sleep apnea syndrome (OSAS) in children referred for sleep-disordered breathing reaches up to 59%. We aimed to test the adequacy of a questionnaire compared to home respiratory polygraphy (HRP), in 45 subjects (5–16 years-old), without maxillofacial malformations nor other comorbidities, presenting with symptoms compatible with OSAS. Methods: All children passed a 12-items questionnaire (Obstructive Airway Child test: OACT) and the HRP. OSAS was classified in severity according to the apnea-hypopnea index (AHI). Results: With HRP, 60% and 15% children were detected to have at least mild (AHI ≥1) and moderate (AHI >5) OSAS, respectively. The sensitivity of the questionnaire to detect mild and moderate OSAS was good (93% and 71%, respectively) but the specificity was very low (11% and 34%). However, an OACT score under 61 showed a very good negative predictive value for moderate and severe OSAS (87%). With the questionnaire, we could have avoided a complementary PSG or HRP in 25/45 (56%) of our subjects as in children with mild OSAS and without comorbidities only clinical observation is usually advised. Conclusions: The OACT questionnaire has shown to be a good and quick instrument to exclude moderate and severe OSAS in our population of children without maxillofacial malformations. Indeed children scoring under 61 could avoid a constraining and expensive sleep exam. However, if the score is above this cut-off, the performance to recognize OSAS is low and the child's evaluation must be completed by a HRP or PSG.